Does education variability change testicular cancer awareness and testicular self examination? - Cenk Murat Yazici; Murat Akgul; Enes Altin; Suleyman Erol Eksi; Tugce Akdemir; Nese Dagdeviren (Journal of the Pakistan Medical Association, 2021)
Objective: Testicular self examination(TSE) is very important for early diagnosis of testicular cancer(TC) In this study, we aimed to investigate the awareness of the TC and TSE at medical school students and normal population. We also compared the awareness of TC and TSE among medical school students according to their educational status. Methods: In order to evaluate the awareness of TC and TSE, we performed a face-to-face questionnaire consisting of 15-questions between January 2019 and April 2019 in Tekirdag. All the participants were selected from the young age group whom the incidence of TC was highest. The study was a comparative study that compared the awareness of TC and TSE and the behaviour of performing TSE between groups. Results: A total of 345 participant were included to study. The awereness of TSE was 52,3% and 23% at medical school students and control group, respectively(p<0,01). Performing TSE was 38,5% and 29,2% at medical school students and control group, respectively(p=0,069). The rate of the awareness of TSE at 1st class medical students was 22,2%, which was increased to 100% at 6th class. Similarly, performing TSE was 18,5% at 1st class students whereas it increased to 81,8% at 6th class. Continuous...